Застосування явища поверхневого плазмонного резонансу для контролю процесу полімеризації оптичних клеїв - Дорожинський, Гліб Вячеславович; Дорожинська, Ганна Василівна; Маслов, Володимир Петрович (Vinnytsia National Technical University, 2019)
A method based on the phenomenon of surface plasmon resonance for real-time control of the polymerization process of optical adhesives is proposed, as demonstrated by the example of the Akrol-3-360 and UV630 photopolymer adhesives. According to the calculated speed and duration of photopolymerization, the UV630 grade adhesive has a 25% higher polymerization rate and almost twice the polymerization time than the Akrol-3-360 grade adhesive.